2013
DOI: 10.1136/annrheumdis-2013-eular.1959
|View full text |Cite
|
Sign up to set email alerts
|

SAT0234 Confirmed High Prevalence of Axial Spondyloarthritis in a Validation Study of Primary Care Patients with Chronic Low Back Pain (Cafaspa-2)

Abstract: Background In 2010 we presented a prevalence of 21% fulfilling the ASAS classification criteria for axial spondyloarthritis (aSpA) in primary care patients with chronic low back pain (CLBP) (CaFaSpA 1 study)1. In addition, a referral model was developed to help general practitioners (GP) to pick up patients at risk for aSpA. If valid, these data might have a considerable impact for GPs, since CLBP is one of the most frequent musculoskeletal complaints in primary care. We therefore replicated the study in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For future cohort studies we believe that similar strategies should be used to identify patients with SpA in primary care. Interestingly, two new studies presented at the American College of Rheumatology 2010 showed similar results regarding the prevalence of axial SpA in primary care 32 33…”
Section: Discussionmentioning
confidence: 80%
“…For future cohort studies we believe that similar strategies should be used to identify patients with SpA in primary care. Interestingly, two new studies presented at the American College of Rheumatology 2010 showed similar results regarding the prevalence of axial SpA in primary care 32 33…”
Section: Discussionmentioning
confidence: 80%